P3_7 Catching Cars - Taylor-Ashley, Jessica; Gregory, Jenny; Garner, Robert; Worthy, Daniel (Physics Special Topics, 2013)
This paper will examine the final stunt in the film 2 Fast 2 Furious where a car, treated as a projectile, drives off a ramp and collides with a speeding yacht. It was calculated that the car travelling at 120mph would travel a distance of 259 metres. The duration of the flight was calculated be 5.5 seconds. In order for this car to collide with a yacht during its motion, the yacht would need to be travelling at 38m/s. This speed is unachievable by even the fastest yachts suggesting the whole scenario is unrealistic.